Dual effects of granular activated carbon on methane enhancement of distillers’ grains in solid-state anaerobic digestion: Restructuring microbial consortia and adsorbing methanogenic substrates - Jiaxing Zhang; Suyue Fan; Ruilin Jiang; Qiuxia Meng; Zhiping Yang; Qiang Zhang; Xing Gao; Wenhai Luo; Min Yan; Guoxue Li (Biomass and Bioenergy, 2027)

Complete genome sequence of a novel Winogradskyella species isolated from deep-sea sponge reveals a β-propeller phytase - Ruilin Fan; Zhenlong Han; Yue Dong; Qinzeng Xu; Sudong Xia; Peiqing He (Marine Genomics, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Complete genome sequencing and analysis revealing assimilatory nitrate reduction pathway of a novel Sphingosinithalassobacter species isolated from the Atlantic hydrothermal sulfides - Han Wu; Ruilin Fan; Chen Han; Yue Dong; Qinzeng Xu; Sudong Xia; Chenlin Liu; Peiqing He (Marine Genomics, 2025)

Experimental study on the combined effect of hydrogen storage tanks and ventilation grilles on the deflagration mechanism in hydrogen-powered ships - Boqiao Wang; Bin Zhang; Yuanchen Xia; Siqi Zhang; Zhuohui Liang; Wenbin Zhu; Ke Ye; Xuexing Fan; Ruilin Song (Ocean Engineering, 2025)

Boosting OER activity of Fe-N Moieties via Ni induced d-Orbital Tailoring for durable rechargeable Zn-Air batteries - Ruilin He; Jinke He; Kang Pu; Qiulin Li; Fan Liu; Qianwei Chen; Wenqian Liu; Hao Chen; Hui Chai; Shu-Juan Bao; Yangyang Tan (Chemical Engineering Journal, 2024)

Geometrically asymmetric pressure sensor with precious few electrodes achieves precise detection of both position and strength by machine learning - Tingkang Yuan; Ruilin Yin; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Study on the mechanism of lignin and lignin-carbohydrate complex hydrolysis under alkaline conditions by density functional theory - Jiahua Mao; Mingfu Zu; Ruilin Wu; Chao Xiao; Jian Kang; Yahong Fan (Biomass and Bioenergy, 2024)

Ti3C2Tx MXene-based all-resistive dual-mode sensor with near-zero temperature coefficient of resistance for crosstalk-free pressure and temperature detections - Tingkang Yuan; Ruilin Yin; Chengwei Li; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2024)

Machine learning powered high-resolution co-seismic landslide detection - Haojie Wang; Limin Zhang; Lin Wang; Ruilin Fan; Shengyang Zhou; Yejia Qiang; Ming Peng (Gondwana Research, 2023)

Fully inkjet-printed dual-mode sensor for simultaneous pressure and temperature sensing with high decoupling - Tingkang Yuan; Ruilin Yin; Chengwei Li; Chao Wang; Zeng Fan; Lujun Pan (Chemical Engineering Journal, 2023)

High- and low- latitude forcing on hydroclimate variability in southern China over the last two millennia - Yun Huang; Jule Xiao; Ruilin Wen; Guoqiang Chu; Luo Wang; Bing Xu; Shengrui Zhang; Jiawei Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Research on target detection of Engraulis japonicus purse seine based on improved model of YOLOv5 - Jiaze Zhang; Shuxian Wang; Shengmao Zhang; Fenghua Tang; Wei Fan; Shenglong Yang; Yongwen Sun; Yang Liu; Wenbin Zhu; Shan Zhang; Ruilin He (Frontiers in Marine Science, 2022)
The refined monitoring and identification of fishing operations by fishing vessels is of great significance and value to fishing vessels. In order to solve the problem of inaccurate statistics of current Engraulis japonicus fishing quota and classification, this paper proposes an improved identification algorithm based on YOLOv5. This method introduces the SENet attention mechanism into the YOLOv5 backbone network structure, integrates the target information in different periods of fishing operations, reduces the interference of complex backgrounds, improves the precision of model detection, and ensures real-time detection efficiency. The artificially shot Engraulis japonicus videos are used as the dataset of the study, and the video is converted into a picture format to realize pre-labeling and processing. The 5550 images are divided into the training set, validation set, and test set according to 8:1:1. In order to verify the validity of the data, a set of in the control experiment, the YOLOv5 backbone network was replaced by MobileNetV2 and the SENet attention mechanism was introduced, and four models were implemented for comparison. The experimental results show that the research algorithm can obtain a mean average precision (mAP) of 99.3%, a precision of 98.9%, and a recall of 98.7%, which are improved by 1.4%, 1.7% and 2.5% respectively compared with the original model. The experimental results match the expectations. According to the statistics of some categories, the Kalman filter and the Hungarian matching method are used to count the main categories of fishing baskets, and an accuracy of 96.5% can be obtained. The threshold method for fishing nets and processing vessels can obtain 85.8% and 75% accuracy. These results shows that this target detection research can provide new ideas for job identification of Engraulis japonicus and provide auxiliary means for job statistics.

Evaluating effectiveness of mitigation measures for large debris flows in Wenchuan, China - Jian He; Limin Zhang; Ruilin Fan; Shengyang Zhou; Hongyu Luo; Dalei Peng (Landslides, 2022)

Contrasting impacts of the 8.2‐ and 4.2‐ka abrupt climatic events on the regional vegetation of the Hulun Lake region in north‐eastern China - Shengrui Zhang; Jule Xiao; Qinghai Xu; Ruilin Wen; Jiawei Fan; Yun Huang; Manyue Li; Jian Liang (Journal of Quaternary Science, 2020)
Studies of the vegetation response to abrupt climatic events may provide valuable insights into assessing the impacts of such events under future global warming scenarios. Here we present a detailed record of regional vegetation change based on high‐resolution pollen records for the intervals 9000–7000 and 5000–3000 cal a bp from the Hulun Lake region of north‐eastern China. Our aims were to determine the regional expression of the 8.2‐ and 4.2‐ka events in north‐eastern China, especially their effects on vegetation composition. The results show that the response of the vegetation of the Hulun Lake region to the climatic cooling of the 8.2‐ka event was relatively minor; however, the 4.2‐ka event, which resulted in climatic aridification, resulted in pronounced vegetation degradation. We suggest that the specific characteristics of the 8.2‐ and 4.2‐ka events, together with their duration and the regional climatic background on an orbital time scale, were the main factors responsible for the contrasting vegetation responses. The strengthening and northward shift of the Intertropical Convergence Zone (ITCZ) tended to offset the cooling effect of the 8.2‐ka event on regional vegetation in the mid–high latitudes of East Asia; in contrast, the decrease in summer insolation in the Northern Hemisphere and the southward shift of the ITCZ may have intensified the drought effect of the 4.2‐ka event in East Asia and the associated vegetation degradation. Under future global warming scenarios, both extreme cooling events and extreme drought events may cause a deterioration of the ecological environment; however, the resulting regional vegetation responses may be substantially different.

Differential transport and preservation of the instars of Limnocythere inopinata (Crustacea, Ostracoda) in three large brackish lakes in northern China - Dayou Zhai; Jule Xiao; Jiawei Fan; Ruilin Wen; Qiqing Pang (Hydrobiologia, 2015)

Spatial heterogeneity of the population age structure of the ostracode Limnocythere inopinata in Hulun Lake, Inner Mongolia and its implications - Dayou Zhai; Jule Xiao; Jiawei Fan; Lang Zhou; Ruilin Wen; Qiqing Pang (Hydrobiologia, 2013)